ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA INDUSTRI PENGOLAHAN DI KOTA SEMARANG ( STUDI KECAMATAN TEMBALANG DAN KECAMATAN GUNUNGPATI ) - Teddy Adhadika; Arif Pujiyono (Universitas Diponegoro, 2014)
ABSTRACT Increasing the amount of labor is not accompanied by an increase in worker performance that will affect the production process and will impede labor productivity. This study aims to analyze the influence of education, wages, incentives, social assurance and work experience on labor productivity in the city of Semarang. This research used primary data and secondary data. Primary data obtained by the method of interviewing a sample of 100 people labor in Tembalang and Gunungpati city of Semarang. Secondary data obtained in the form of a ready-made form of publication such as the data from the Central Bureau of Statistics (BPS) Jawa Tengah. The analysis tool used is the mathematical models Multiple Linear Regression by SPSS 17.0 program. The results showed that, only four variables that significantly affect the productivity of labor, education, wages, incentives and work experience, the social was not significant. Coefficient of determination value of 0.823 which means that labor productivity can be explained by the variable factors of education, wages, incentives and work experience is 82,3 percent. While the remaining 17,7 percent of labor productivity can be explained by other variables that is not included in the analysis model in this research.